Efficient, Solvent-Free and Rapid Oxidation of Alcohols to Carbonyl Compounds with N,N’-Dibromo-N,N’-1,2-ethanediylbis(benzene sulfonamide) - Mahboubifar, M.; Khazaei, A.; Rostami, A. (Asian Journal of Chemistry, 2010)
N,N'-Dibromo-N,N'-1,2-ethanediylbis(benzene sulfonamide) (BNBBS): a safe, neutral and efficient reagent was utilized for the rapid and selective oxidation of alcohols to carbonyl compounds with no side reactions such as oxidations of carbon-hydrogen bonds, over oxidation of aldehydes and bromination of aromatic rings; under solvent-free condition, at room temperature with excellent yield.